Upaya Peningkatan Kualitas Lingkungan Keluarga terhadap Perilaku Sosial Anak Usia Dini - Intan Dwi Wahyuni (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2025)
Early childhood education plays a crucial role in shaping children’s character and social behavior. The family serves as the first and foremost environment in which children develop their social interactions. This article aims to describe the relationship between family environment quality and the social behavior of early childhood, as well as strategies to improve the family environment that supports children’s social development. This study used a library research method by analyzing books, journals, and previous studies. The results showed that a high-quality family environment characterized by effective communication, affection, emotional support, and positive parenting could foster children’s social behavior such as empathy, cooperation, and respect. Conversely, families with conflict or lack of attention can hinder social development. Efforts to improve the family environment can be made through parenting education, collaboration between early childhood institutions and families, and the involvement of nonformal education. Therefore, improving the quality of the family environment is a strategic step in fostering healthy and adaptive social behavior in early childhood.